Microscopic biliary and perineural invasion and clinical outcome after neoadjuvant bevacizumab-based chemotherapy and liver resection in patients with colorectal liver metastases. Issue 1 (January 2018) - Stift, Judith; Graf, Alexandra; Schwarz, Christoph; Tamandl, Dietmar; Starlinger, Patrick; Herac, Merima; Beer, Andrea; Wrba, Friedrich; Bodingbauer, Martin; Kaczirek, Klaus; Stremitzer, Stefan
Abstract: Background: The value of microscopic biliary and perineural invasion as prognostic biomarkers in patients with resectable colorectal liver metastases (CLM) who undergo neoadjuvant chemotherapy and liver resection is still unclear. This retrospective study was performed to elucidate this issue. Methods: Histologic slides of resected CLM of patients who underwent neoadjuvant bevacizumab-based chemotherapy and liver resection were investigated with respect to biliary and perineural invasion. Presence of invasion was correlated with radiologic and histologic response, recurrence-free survival (RFS) and overall survival (OS). Results: One hundred forty-one patients were enrolled. There was a significant association between biliary and perineural invasion, respectively ( P = 0.001). Moreover, both biliary and perineural invasion were associated with bilobar metastatic spread and higher number of metastases, while perineural invasion was also associated with a higher Fong score. No significant association was found with response. In univariable analysis, biliary and perineural invasion were associated with shorter RFS (median 10.1 vs. 13.5 months, HR 2.09, P = 0.010 and 7.6 vs. 14.0, HR 2.23, P = 0.001, respectively). Biliary invasion was also associated with shorter OS (median 32.8 months vs. not reached, HR 2.78, P = 0.010), however these results did not remain significant in multivariable analysis. Conclusions: In patients with resectable colorectal liver metastases undergoing neoadjuvant bevacizumab-based chemotherapy and liver resection, biliary and perineural invasion are associated with higher tumor load but may not be prognostic biomarkers.